Hubungan Riwayat Kunjungan ANC, Paritas Dan Pendidikan Dengan Kejadian BBLR Di Klinik Pratama Mariana - Purba , Firda Rebiani Br.; Hanum, Parida; Sinaga , Junita Maria Medelina; Rafianef, Ghina Zahwa; Sianturi, Firnawi (Journal of Pharmaceutical and Sciences, 2025)
Background: Low Birth Weight (LBW) infants are those born with a weight of less than 2,500 grams. The incidence of LBW can be influenced by several risk factors, including antenatal care (ANC) visit history, parity, maternal education level, and employment. Objective: This study aimed to examine the relationship between ANC visit history, parity, and education level with the incidence of LBW at Klinik Pratama Mariana in 2024. Methods: This was a quantitative study with a retrospective design. Data were collected using total sampling through observation sheets and questionnaires completed by respondents. The study population consisted of 55 mothers who gave birth at Klinik Pratama Mariana Tanjung Gusta, with the sample including those who delivered LBW infants. Data were analyzed using univariate and bivariate analyses with the chi-square statistical test. Results: The results showed a significant relationship between irregular ANC visits and the incidence of LBW (p-value = 0.000). High parity (≥3) also showed a significant association with LBW incidence, observed in 92% of respondents (p-value = 0.000). Furthermore, low educational level (<senior high school) was significantly associated with LBW, found in 85% of respondents (p-value = 0.000). Conclusion: There is a significant relationship between ANC visit history, parity, and maternal education level with the incidence of LBW. Health workers are expected to enhance monitoring and provide counseling for pregnant women with risk factors to help prevent LBW.